2020
DOI: 10.1002/hep4.1509
|View full text |Cite
|
Sign up to set email alerts
|

High Protein Intake Is Associated With Histological Disease Activity in Patients With NAFLD

Abstract: Overconsumption of carbohydrates and lipids are well known to cause nonalcoholic fatty liver disease (NAFLD), while the role of nutritional protein intake is less clear. In Western diet, meat and other animal products are the main protein source, with varying concentrations of specific amino acids. Whether the amount or composition of protein intake is associated with a higher risk for disease severity has not yet been examined. In this study, we investigated associations of dietary components with histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…There are few data related to the effect of protein consumption on the development of NAFLD, and the results obtained are quite heterogeneous. It has been reported that high protein intake could have a negative, neutral, or even positive effect on NAFLD [ 125 , 126 , 127 , 128 ]. The best explanation for this controversy is that animal and vegetable proteins could exert opposite effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few data related to the effect of protein consumption on the development of NAFLD, and the results obtained are quite heterogeneous. It has been reported that high protein intake could have a negative, neutral, or even positive effect on NAFLD [ 125 , 126 , 127 , 128 ]. The best explanation for this controversy is that animal and vegetable proteins could exert opposite effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intervention and observational studies on the relationship between protein and NAFLD show conflicting results. Some studies found evidence that higher protein intakes might have a negative effect on NAFLD, while other studies showed a neutral or positive effect [ 125 , 126 ]. These inconsistencies might be explained by the type of protein consumed, as animal protein seems to have a negative effect on NAFLD, while plant protein has an inverse association [ 125 ].…”
Section: Nutrition and Nafldmentioning
confidence: 99%
“…The 16S ribosomal RNA gene sequencing of human stool samples was performed as previously described. 28…”
Section: Bacterial Dna Extraction and 16s Ribosomal Rna Sequencingmentioning
confidence: 99%
“…A recent study analyzed the effects of isocaloric diets rich in animal proteins or plant proteins for 6 weeks in patients with diabetes and NAFLD and found that both high-protein diets reduced liver fat [ 68 ]. However, high consumption of proteins and of red and/or processed meat has been reported in patients with NASH [ 69 , 70 ]. The Rotterdam study further showed that a high animal protein intake is associated with a higher prevalence of hepatic steatosis in overweight and elderly patients [ 71 ].…”
Section: Introductionmentioning
confidence: 99%